Color‐Changing Biomimetic Films: Natural Light‐Scattering Nanoparticles Enable Visible through Short‐Wave Infrared Color Modulation (Advanced Optical Materials 8/2018). Issue 8 (18th April 2018) - Kumar, Amrita; Osgood, Richard M.; Dinneen, Sean R.; Koker, Brian D.; Pang, Richard; Deravi, Leila F.
Abstract : An unlikely source for tunable visible through infrared light scattering emerges from nanoparticles isolated and processed from squid skin, as shown by Leila F. Deravi and co‐workers in article number1701369 . Color and brightness in the mimetic films and fibers are controlled by varying particle layer thicknesses and by combining a back‐reflector with a specific band pass, illustrating new materials applications for these biological nanostructures.